Respuesta :

Answer:

x = -6/5

Step-by-step explanation:

Note that 2 log-to-the-base-2 of 3 is equivalent to log-to-the-base-2 of 3^2, or log-to-the-base-2 of 9.

Also:  log-to-the-base-2 of 9  +  log-to-the-base-2 of (x + 1) is equivalent to

log-to-the-base-2 of 9(x + 1), and thus we have:

log-to-the-base-2 of 9(x + 1) = log-to-the-base-2 of (4x + 3)

And so:

  log-to-the-base-2 of 9(x + 1)         log-to-the-base-2 of (4x + 3)

2                                                  =  2

Because this is true, we can conclude that 9(x + 1) = (4x + 3).

Combining like terms results in 5x + 9 = 3, or   5x = -6.  Then x = -6/5